The roles of molecular chaperones in bacterial infection - Yamamoto, Tomoko (Henry Stewart Talks, 2007)
Discovery of major molecular chaperones through the studies on bacteriophage lambda, Discovery of function of DnaK machinery assisting assembly/disassembly of macromolecule protein structure, Roles of DnaK chaperone machinery and ClpX chaperone in Salmonella pathogenesis and flagellar biogenesis, Role of GroEL on bacterial cell surface
Updated at 2018/04/30